Childhood brand nostalgia: A new conceptualization and scale development. Issue 4 (25th April 2016) - Shields, Alison B.; Johnson, Jennifer Wiggins
Abstract: This research seeks to expand the current understanding of nostalgia towards childhood as it relates to consumer brand relationships and provide a framework for better understanding the phenomenon as it appears in both academic and real‐world settings. In this paper, the authors use existing literature on nostalgia and consumer interviews to define childhood brand nostalgia as a positively valenced emotional attachment to a brand because of the brand's association with fond memories of the individual's non‐recent lived past . A scale to measure an individual's childhood brand nostalgia is developed and tested to ensure convergent, discriminant, and predictive validity. The scale is found to capture individual differences in nostalgic feelings towards a single brand, and individuals are found to have varying levels of nostalgic feelings for multiple brands across multiple product categories. This demonstrates the usefulness of this scale in determining a consumer's nostalgia towards a particular brand from their childhood. Copyright © 2016 John Wiley & Sons, Ltd.